Striatal dopamine neurotransmission: regulation of release and uptake - Sulzer, D; Cragg, S; Rice, M (Elsevier, 2016)
Dopamine (DA) transmission is governed by processes that regulate release from axonal boutons in the forebrain and the somatodendritic compartment inmidbrain, and by clearance by the DA transporter, diffusion, and extracellular metabolism. Wereview how axonal DA release is regulated by neuronal activity and by autoreceptors and heteroreceptors, and address how quantal release events are regulated in size and frequency. In brain regions densely innervated by DA axons, DA clearance is due predominantly to uptake by the DA transporter, whereas in cortex, midbrain, and other regions with relatively sparse DA inputs, the norepinephrine transporter and diffusion are involved. We discuss the role of DA uptake in restricting the sphere of influence of DA and in temporal accumulation of extracellular DA levels upon successive action potentials. The tonic discharge activity of DA neurons may be translated into a tonicextracellular DA level, whereas their bursting activity can generate discrete extracellular DA transients.